Performance of early maturity soybean cultivars in nutrient solution containing different levels of manganese - Mascarenhas, Hipólito Assunção Antonio; Miranda, Manoel Albino Coelho de; Tanaka, Roberto Tetsuo; Falivene, Sonia Maria Pierro; Dechen, Antonio Roque (Pesquisa Agropecuaria Brasileira, 2014)
In Brazilian soils the occurrence of manganese toxicity problems is more frequent than deficiency. With this in mind, six soybean cultivars (IAC-Foscarin 31, Davis, BR-4, BR-6, Bragg, IAS-5, IAC-13 and Paraná) were tested in a nutrient solution containing four levels of manganese (0,11; 2; 4 and 6 mg/l) under constant temperature of 25 ± 1°C. Tolerance was measured taking into consideration the dry matter weight of the nerial parts after 15 days in nutrient solution, visual symptoms of toxicity, and the concentration of the Mn in the aerial parts. The results showed that the Davis and IAC-Foscarin 31 cultivars were tolerant, whereas Bragg, IAS-5, BR-4, BR-6 and IAC-13 were intermediate, and the cultivar Paraná very sensitive to high Mn concentrations. The scores given for visual symptoms of toxicity concides negatively with the data of dry matter weight of the plants, and positively with the manganese absorbed. This method was considered to be practical when one deals with great quantity of breeding limes in a soybean breeding program.